A Glance at the Past and a Glimpse of the Future. (March 2020) - Vickery, Barry
Abstract: This article represents a summary of the parallel session that Barry Vickery presented to delegates at the 2019 BIALL Annual Conference in Bournemouth. There, his presentation was entitled: 'A glance at the past and a glimpse of the future – How to learn from the past to make better decisions in the future'. As BIALL was celebrating its 50th anniversary, Barry took the opportunity to look back at the last fifty years to highlight people and companies that had made good decisions and those that had made bad ones. He went on to explore different decision-making techniques that we could all utilise to help us to make more informed decisions in our daily life.